2011
DOI: 10.1592/phco.31.11.1145
|View full text |Cite
|
Sign up to set email alerts
|

Liver Failure Requiring Transplantation After Orlistat Use

Abstract: Orlistat is a United States Food and Drug Administration (FDA) approved medication indicated for the management of obesity. The FDA has issued a warning of rare, but severe, reports of liver injury following orlistat use. We report the case of a 40 year old female, with no prior medical history, who experienced fulminant liver failure following orlistat use. She presented to our center with severe cholestasis and coagulopathy. Liver ultrasound, serologies for viral hepatitis, and autoimmune markers were unrema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is important to note that orlistat has predominant gastrointestinal side effects. Moreover, the postmarketing review by the US FDA identified 13 cases of severe liver injury associated with orlistat [40]. Therefore, orlistat interventions in patients with advanced liver disease should be performed with caution.…”
Section: Lifestyle Modifications and Antiobesity Medicationsmentioning
confidence: 99%
“…It is important to note that orlistat has predominant gastrointestinal side effects. Moreover, the postmarketing review by the US FDA identified 13 cases of severe liver injury associated with orlistat [40]. Therefore, orlistat interventions in patients with advanced liver disease should be performed with caution.…”
Section: Lifestyle Modifications and Antiobesity Medicationsmentioning
confidence: 99%
“…Worsening liver failure occurred over a period of 8 weeks and ultimately required liver transplantation. Although the liver copper concentration was elevated in this case, additional work-up was negative for Wilson's disease and orlistat was deemed to be the most likely aetiology of liver failure (20). In all above-mentioned cases, other plausible aetiologies of liver failure such as viral infection, autoimmune and vascular diseases were ruled out.…”
Section: Discussionmentioning
confidence: 72%
“…Orlistat is an intestinal lipase inhibitor drug that is recommended in obese patients along with a hypocaloric diet (1). Although the most frequent secondary effect is steatorrhea, fulminant liver failure has also been associated with this drug, which has required liver transplantation in 3 patients (2)(3)(4). We present the case of a 42-year-old obese male who was being treated for hypertension, of 183 cm in height and 131 kg in weight with a BMI of 39.12.…”
mentioning
confidence: 99%